Utilization of rice husks as effective bioadsorbents for methylene blue removal from wastewater: characterization, adsorption performance, and regeneration studies - Hadid Sukmana; Milivoj Radojčin; Tamás Gyulavári; Gábor Kozma; Zoltán Kónya; Cecilia Hodúr (Applied Water Science, 2025)
Abstract Dye wastewater contains dangerous chemical compounds, posing hazards to human health and the environment. This study investigates the efficacy of Hungarian rice husk (HRH) and Indonesian rice husk (IRH) as bioadsorbents for removing methylene blue (MB) from wastewater. The raw rice husks (RHs) were modified via hydrothermal carbonization to enhance adsorption efficiency. Characterization of the RHs was conducted through zeta potential measurements, Fourier transform infrared spectroscopy, and scanning electron microscopy. Batch adsorption experiments were carried out to evaluate the influence of various parameters, including pH, adsorbent dose, initial dye concentration, adsorbent particle size, and contact time on adsorption. The results indicate that the maximum dye removal was achieved at a contact time of 60 minutes. Hydrochar rice husks demonstrated slightly higher removal efficiencies than their raw rice husks. Adsorption kinetics followed the Elovich model, while the BET multilayer isotherm model provided a superior fit to the experimental data for MB adsorption. The simulation of the monolayer adsorption model indicated that the Langmuir isotherm provided the best fit for the experimental adsorption data. The adsorption capacities of HRH and IRH were 52.23 mg/g and 47.92 mg/g, respectively. The regeneration of RHs after adsorption–desorption cycles required using hydrochloric acid as a desorbing solution in four cycles. The recovered MB dye was reused for coloring cotton fabrics with ΔE* color values consistently below 5, indicating acceptable color differences. These findings suggest that RHs possess considerable potential as bioadsorbents for removing MB from wastewater.